Модифікуючий вплив присадок на термін заміни моторної оливи в нестаціонарних умовах експлуатації - Слонь, В. В.; Slon', Viktor (КНТУ, 2015)
Розглянута проблема підвищення надійності транспортних засобів, що працюють в нестаціонарних умовах експлуатації та вплив режимів їх роботи на термін заміни моторної оливи. Охарактеризовано вплив зміни властивостей моторної оливи на її показники якості. Наведені результати експериментальних досліджень впливу модифікування моторної оливи присадками дисульфід молібдену, "Roil Gold", "КГМТ-1" на швидкість надходження та концентрацію заліза з напрацюванням. Виявлено поліпшення показників якості моторної оливи і подовження терміну її експлуатації. The aim of this work is to study the impact modifying additives to change the speed of receipt and concentration of iron in the motor oil, vehicle operating in non-stationary conditions. The problem of improving the reliability of vehicles operating in non-stationary conditions and the impact of their operation modes for up replacing the engine oil. The characteristic types of unsteady operating conditions, depending on the environmental conditions, climate, traffic, mining conditions, operating conditions, are defined by their main parameters. Demonstrated techniques for obtaining and processing the results of experimental studies. The influence of changes in the properties of motor oil in its quality and condition of engine oil determined by the contents of her metal wear products, by method sprektrografii. The results of experimental studies of the effect of modification of motor oil additives molybdenum disulfide, "Roil Gold", "КГМТ-1" to speed receipt and concentration of iron and operating time of diesel vehicles. Found improvement in the quality of motor oil and the extension of its operation.
Impact modifying additive term replacement of engine oil in non-stationary conditions
Keywords: моторна олива; транспортний засіб; двигун; режим роботи; нестаціонарні умови; експлуатація; напрацювання; присадки; motor oil; vehicle; engine; non-stationary conditions; exploitation; operating time; additives